Respuesta :
The distance between any two points is:
d^2=(x2-x1)^2+(y2-y1)^2 so in this case:
d^2=(7-4)^2+(-3-6)^2
d^2=3^2+9^2
d^2=90
d=√90
d=3√10 units
d≈9.49 units (to nearest hundredth of a unit)
d^2=(x2-x1)^2+(y2-y1)^2 so in this case:
d^2=(7-4)^2+(-3-6)^2
d^2=3^2+9^2
d^2=90
d=√90
d=3√10 units
d≈9.49 units (to nearest hundredth of a unit)
Answer:
As shown in the image....
Step-by-step explanation:
This equation follows with the distance formula which is (x2-x1)+(y2-y1) squared.
![Ver imagen Bestflashcardbuilder](https://us-static.z-dn.net/files/d7b/0d87f1651cd04b12aa0fe8e0ac67a1de.png)